Kiat Praktis Pengintegrasian Aplikasi Publish or Perish (PoP) dengan Aplikasi Mendeley - Rian Dani; Bima R. Dani; Armandito Armandito; Shandy Amandha; Dhea Lova (Institut Nalanda, 2025)
This Community Service Activity (PKM) discusses the integration of the Publish or Perish (PoP) application as a source of scientific literature search and the Mendeley application that can help students avoid common mistakes in writing citations or bibliographies, such as mistakes in writing the author's name or year of publication. The purpose of this community service activity is to provide knowledge, understanding and direct practice to students about the integration of the Publish or Perish (PoP) application with the Mendeley application. The methods used are demonstration methods, lectures and questions and answers. The results of this Community Service Activity (PKM) students are able to integrate the Publish or Perish (PoP) application with the Mendeley Application, so that the results of references from the Publish or Perish (PoP) application will be registered in the Mendeley Application and it will make it easier for students to create a Bibliography without adding references one by one.